An exploration study of RimbaIlmu: A qualitative evaluation of shared single display groupware in Sarawak, Malaysia - WaiShiang, C.; Mit, E.; Lu, M. (Kassel University Press GmbH, 2015)
Shared single display groupware that enables collaboration among people from different cultures and social practices encourages peer learning and teaching, whilst strengthening communication skills. It has been successfully evaluated in remote schools in China and India. Due to this, the question arises whether it can be deployed in rural schools or semi-urban schools in Sarawak? What are the issues and challenges? What are the impact of this technology among the students and teachers? This paper investigates the deployment of shared single display groupware in rural and semi-urban schools in Sarawak (one of the Malaysian states). We introduce a shared single display application, RimbaIlmu, in one semi-urban school and one rural school and conduct qualitative analysis from the observations among the participants. Observational data has shown that RimbaIlmu is able to stimulate collaboration between different genders; an engaging technology among students; a tool for group and individual assessment; a tool to facilitate leadership skills; fun to play with; allows ease of lab management and control; enabling novices to learn computers; promoting membership in collaboration learning and finally provide environment for task accomplishment with minimum teacher intervention.